Free calcium induces degenerative changes in the intervertebral disc through the calcium sensing receptor. (3rd June 2015) - Rakan, B; AlGarni, N; Salem, O; Epure, L; Habis, AA; Antoniou, J; Mwale, F; Grant, M
Abstract : Introduction: Degenerative disc disease (DDD) is a common cause of lower back pain. Calcification of the intervertebral disc (IVD) has been correlated with DDD. The role of IVD calcification in the development DDD is unknown. We noticed an increase in ionic calcium content and expression of the extracellular calcium-sensing receptor (CaSR) in the degenerate discs, however, its role in DDD remains unclear. Material and Methods: IVD Cells: Bovine and human NP and AF cells were incubated in culture media supplemented with various concentrations of calcium, and a CaSR agonist IVD Cultures: IVDs from bovine tails were isolated and the vertebral bone was removed. IVDs were cultured for 6 weeks in culture medium supplemented with calcium (1.0, 2.5, or 5.0 mM), or a CaSR agonist. Western blotting was performed on extracts to assess for aggrecan and Col II. Results: The expression of aggrecan and Col II decreased dose-dependently in both NP and AF cells, as well as in the organ culture model following supplementation with calcium or the CaSR agonist. Conclusion: Our results suggest that changes in the local concentrations of calcium are not benign, and that activation of the CaSR may be a contributing factor in IVD degeneration.